Sialylation on O-linked glycans protects von Willebrand factor from macrophage galactose lectin-mediated clearance - Soracha E. Ward; Jamie M. O’Sullivan; Alan B. Moran; Daniel I. R. Spencer; Richard A. Gardner; Jyotika Sharma; Judicael Fazavana; Marco Monopoli; Thomas A.J. McKinnon; Alain Chion; Sandra Haberichter; James S. O’Donnell (Haematologica, 2021)
Terminal sialylation determines the plasma half-life of von Willebrand factor (VWF). A role for macrophage galactose lectin (MGL) in regulating hyposialylated VWF clearance has recently been proposed. In this study, we showed that MGL influences physiological plasma VWF clearance. MGL inhibition was associated with a significantly extended mean residence time and 3-fold increase in endogenous plasma VWF antigen levels (P<0.05). Using a series of VWF truncations, we further demonstrated that the A1 domain of VWF is predominantly responsible for enabling the MGL interaction. Binding of both full-length and VWF-A1-A2-A3 to MGL was significantly enhanced in the presence of ristocetin (P<0.05), suggesting that the MGL-binding site in A1 is not fully accessible in globular VWF. Additional studies using different VWF glycoforms demonstrated that VWF O-linked glycans, clustered at either end of the A1 domain, play a key role in protecting VWF against MGLmediated clearance. Reduced sialylation has been associated with pathological, increased clearance of VWF in patients with von Willebrand disease. Herein, we demonstrate that specific loss of α2-3 linked sialylation from O-glycans results in markedly increased MGL-binding in vitro, and markedly enhanced MGL-mediated clearance of VWF in vivo. Our data further show that the asialoglycoprotein receptor (ASGPR) does not have a significant role in mediating the increased clearance of VWF following loss of O-sialylation. Conversely however, we observed that loss of N-linked sialylation from VWF drives enhanced circulatory clearance predominantly via the ASGPR. Collectively, our data support the hypothesis that in addition to regulating physiological VWF clearance, the MGL receptor works in tandem with ASGPR to modulate enhanced clearance of aberrantly sialylated VWF in the pathogenesis of von Willebrand disease.